(untitled) (Research, Society and Development, 2020)
A mesquite tree (Prosopis juliflora), is one of the most abundant species in the Brazilian semiarid region. Its pods are called mesquite and have a sweet taste and aroma, due to the elevated sucrose content, in addition, they are a rich source of fibers that can be used as raw material for the elaboration of a series of food products and technological innovations. In view of this, the objective was to develop and characterize the physicochemical characteristics of different formulations of cookies added to mesquite flour. For this, mesquite flour was prepared and then three cookie formulations, as follows: CC: control cookie without mesquite flour, C10 and C20, cookie with 10% and 20% of mesquite flour, respectively. The physical-chemical analyzes performed were moisture, ash, acidity, pH and water activity in the prepared cookies. The results showed a moisture content of 1.17; 2.51 and 1.94%, ash content of 1.48; 1.5 and 1.66%, acidity of 0.22; 0.18 and 0.23%, pH 6.5; 6.7 and 7.4 and water activity of 0.1860; 0.2790 and 0.2420 for CC, C10 and C20, respectively. It’s concluded that the cookies presented satisfactory physical-chemical results when compared with the Brazilian legislation. It is also worth mentioning that the use of mesquite flour is promising in the preparation of cookies.